Liebe und Tod im Ersten (Alten) Testament (lectio difficilior, 2004)
Taking as her starting point the programmatically formulated power of love to resist death (Song of Songs 8,6f), the author first explores possible meanings of "death" and "love" in the Hebrew Bible, and next the mythological and literary-historical background of these verses. Their plausibility and impact are grounded, on the one hand, in mythological traditions about goddesses from Egypt and Ugarit, who pluck life from the jaws of death, and on the other hand, in the continuation of this ideal inheritance in the literature of Israel: women resist death with their love. However, as the stories about David and Jonathan demonstrate, also the love of men, represented in this way, does not leave death the last word.